PERCEPTIONS OF MEDICAL STUDENTS ABOUT RESEARCH AT UNDERGRADUATE LEVEL - Arshad, Saamia; Huda, Noor ul; Nadeem, Nayha; Ali, Sobia; Ahmad, Naveed; Anwar, Saeed; Mustafa, Mohammad; Riaz, Nayab; Waheed, Mustafeez; Toori, Junaid Khan (Journal of Ayub Medical College Abbottabad, 2021)
Background: Undergraduate (UG) research is new but important concept in modern science. It is considered as an effective educational tool for enhancing the undergraduate medical experience. The objectives of the study were to know the perceptions of UG medical students towards research, main motivating factors and barriers faced by the students. Methods: It was Cross-sectional study with both quantitative and qualitative portions conducted in Ayub Medical College (AMC) from November 2018 to April 2019. The quantitative portion of the study was based on a simple questionnaire with 9 closed ended questions completed by 215 participants selected using stratified random sampling technique. Data was analysed using SPSS 20.0. The Qualitative portion of the study was based on 8 Focused Group Discussions (FGDs), two from each year, with 6-10 participants. The interviews were recorded and reported by obtaining informed consent from each participant. The audio recording of the FGDs was transcribed verbatim and content analysis was done by conventional content analysis. Results: Out of 215, 128 (59.5%) had a previous research experience mostly as a compulsory requirement of undergraduate curriculum; 134 (62.3%) were aware that research is a part of their curriculum. Lack of resources and lack of interest of students was main barrier, i.e., 152 (70.7%). For 133 (61.8%) participants, the main motivating factor was learning research methodology. Conclusions: Students were aware about research and their awareness about research increased with increasing year in medical school. Hardly any student had a research experience beforehand they took part in mandatory research in 4th year. Keywords: Medical undergraduates; Undergraduate research